Chronostratigraphic model of a high-resolution drill core record of the past million years from the Koora Basin, south Kenya Rift: Overcoming the difficulties of variable sedimentation rate and hiatuses. (1st July 2019) - Deino, A.L.; Dommain, R.; Keller, C.B.; Potts, R.; Behrensmeyer, A.K.; Beverly, E.J.; King, J.; Heil, C.W.; Stockhecke, M.; Brown, E.T.; Moerman, J.; deMenocal, P.; et al.
Abstract: The Olorgesailie Drilling Project and the related Hominin Sites and Paleolakes Drilling Project in East Africa were initiated to test hypotheses and models linking environmental change to hominin evolution by drilling lake basin sediments adjacent to important archeological and paleoanthropological sites. Drill core OLO12-1A recovered 139 m of sedimentary and volcaniclastic strata from the Koora paleolake basin, southern Kenya Rift, providing the opportunity to compare paleoenvironmental influences over the past million years with the parallel record exposed at the nearby Olorgesailie archeological site. To refine our ability to link core-to-outcrop paleoenvironmental records, we institute here a methodological framework for deriving a robust age model for the complex lithostratigraphy of OLO12-1A. Firstly, chronostratigraphic control points for the core were established based on 40 Ar/ 39 Ar ages from intercalated tephra deposits and a basal trachyte flow, as well as the stratigraphic position of the Brunhes-Matuyama geomagnetic reversal. This dataset was combined with the position and duration of paleosols, and analyzed using a new Bayesian algorithm for high-resolution age-depth modeling of hiatus-bearing stratigraphic sections. This model addresses three important aspects relevant to highly dynamic, non-linear depositional environments: 1) correcting for variable rates of deposition, 2) accommodating hiatuses, and 3) quantifying realistic age uncertainty with centimetric resolution. Our method is applicable to typical depositional systems in extensional rifts as well as to drill cores from other dynamic terrestrial or aquatic environments. We use the core age model and lithostratigraphy to examine the interconnectivity of the Koora Basin to adjacent areas and sources of volcanism. Highlights: Innovative age model based on new Pleistocene drill core record from south Kenya Rift. Geochronology uses control points from tephra 40 Ar/ 39 Ar ages and magnetostratigraphy. Bayesian algorithm corrects for variable rates of deposition and paleosol hiatuses. Age model chronostratigraphy sets a new standard for calibrating drill core records.